Blunt Traumatic Left Anterior Descending Artery Dissection - Upreti, Dinesh; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Shakya, Samir; Chimoriya, Romila; Thapa, Shovit; Thapa, Sanjeev; Manandhar, Bhawani; Yadav, Vijay; et al. (Nepalese Heart Journal, 2025)
Background: Coronary artery dissection is a rare and life-threatening event resulting after blunt trauma especially in setting of high-speed motor vehicle collision. It can result in acute coronary syndrome due to subsequent thrombus formation, propagation of dissection, and total occlusion of coronary artery. Case: A thirty-year-old male sustained high speed motorbike collision resulting in closed right sub-trochanteric fracture and right mid clavicle fracture. While being evaluated for surgery, he developed heart failure and further cardiac evaluation was done. Coronary computed tomography angiography was done which revealed dissection of proximal left anterior descending artery and percutaneous coronary intervention (PCI) was attempted in view of refractory ventricular tachycardia. After unsuccessful PCI, off-pump coronary artery bypass grafting was done with successful revascularization and electrical stabilization. Conclusion: This highlights the importance of considering coronary artery dissection in patients with blunt chest trauma.